Terminal agitation: the Delphi method for a symptom severity measurement tool - Hirschinger, Hanna; Hetjens, Svetlana; Thanbichler, Eric; Hofmann, Wolf-Karsten; Gencer, Deniz; Boch, Tobias (BMJ Supportive & Palliative Care, 2025)
Objectives The effectiveness of treatment interventions should be evaluated using measurement tools tailored to the research objective, the user’s needs and the complexity of the symptom being assessed. In palliative care, assessing terminal agitation remains challenging due to the limited availability of validated and practical tools. This research aimed to systematically develop, validate and implement a symptom score for terminal agitation that is both scientifically sound and suitable for routine clinical use. The goal was to enable objective monitoring of symptom progression and evaluation of pharmacological interventions. - Methods A structured Delphi method was used to develop a four-point Numerical Rating Scale (NRS) for assessing the severity of terminal agitation. The five-phase process incorporated iterative expert feedback to ensure clarity, relevance and clinical applicability. The resulting scale was validated using five clinical case scenarios rated by 10 experienced palliative care professionals. - Results The Delphi process yielded a 94% consensus in favour of the proposed NRS. A total of 250 ratings were submitted during validation, of which 218 (87%) matched the predefined reference solution. Of the 32 (13% from 250) mismatches, 12 (38%) were overestimations and 20 (63%) underestimations. The majority of deviations (29 of 32) differed by only one point on the scale. - Conclusion By achieving expert consensus, the description of terminal agitation severity can be objectified, enhancing the reliability of assessment in palliative care. The validated NRS provides a standardised tool to support objective clinical decision-making and improve symptom management in terminally ill patients.
Gesehen am 12.01.2026